Comparison between the Effect of Thai Herbal Steam and Conventional Steam Baths on Body Flexibility - Kumfu, Sirintip; Hanphithakphong, Panida; Sittitan, Maitip; Udomkitpakorn, Palagon; Wongkhumdeang, Nattapol; Srisang, Duangkamon; Noisakul, Ratchanok; Kunchai, Tassanee; Sarika, Prapaipak; Intama, Ornanong (Srinagarind Medical Journal, 2016)
Background and Objective : One factor that contributes to muscle injuries from work is the lack of body flexibility. Herbal steam is one of a way to treat muscle fatigue. However, no studies have determined the effect of herbal steam on body flexibility. The purpose of this study was to compare the effect of Thai traditional herbal steam and normal steam on flexibility in female. Methods : Twenty-six females who have low to moderate of lower back and hamstring muscle flexibility were participated. Low to moderate of lower back and hamstring muscle flexibility were determined by sit and reach test less than 12 cm. while those of shoulder muscle groups were determined by shoulder girdle flexibility test less than +2 cm. Participants were randomly assigned into two groups: 13 participants received Thai herbal steam and 13 participants received normal steam. The steam bath program was 2 weeks, 3 times per week and 30 minutes per time. Flexibility was measured at pre- and post-steam bath programs. Results : Thai herbal steam group had increased flexibility of lower back and hamstring muscles more than normal steam group (p=0.03). At baseline flexibility of lower back and hamstring muscles in normal steam group was 3.12 ± 5.69 cm. and Thai herbal steam group was 4.73 ± 6.15 cm. Post-steam bath program in normal steam group was 7.92 ± 5.14 cm. and Thai herbal steam group was 12.87 ± 6.19 cm. Conclusion: Thai herbal steam could be increased flexibility of lower back and hamstring muscles in women than normal steam.